Driving Analytics – Data Science Approach based on Smartphone Vehicle Telematic Data - S. S. Syed Ahmad; M. Muhammad; Z. M. Jawi (Journal of the Society of Automotive Engineers Malaysia, 2022)
Driving takes place in the everyday life of many people around the globe. Driving analytics adaptations might increase overall security and lessen vehicle energy consumption and gas emissions. In this context, driver analytics and profiling try to better understand and potentially improve driver behavior, leveraging safer and more energy- aware driving. Driver monitoring and analysis or driver behavior profiling is the process of automatically collecting driving data (e.g., speed, acceleration, braking, steering, location) and applying a data science approach to generate a safety score for the driver.